Sumberdaya Alam dan Pemanfaatannya di Situs Biaro Sipamutung, Padang Lawas Utara, Sumatera Utara (Kajian Laboratoris) - Muh. Fadlan S. Intan (Berkala Arkeologi Sangkhakala, 2010)
AbstractIn the area of Padang Lawas, there are many biaros as the archaeological remains, especially along DAS Barumun and DAS Batang Pane. The existence of various remains in the region due to the availability of natural resources needed by human to his life. Various existing natural resources are exploited by people with supported by its own technology.